Axon growth and synaptic function: A balancing act for axonal regeneration and neuronal circuit formation in CNS trauma and disease. Issue 7 (28th September 2020) - Kiyoshi, Conrad; Tedeschi, Andrea
Abstract: Axons in the adult mammalian central nervous system (CNS) fail to regenerate inside out due to intrinsic and extrinsic neuronal determinants. During CNS development, axon growth, synapse formation, and function are tightly regulated processes allowing immature neurons to effectively grow an axon, navigate toward target areas, form synaptic contacts and become part of information processing networks that control behavior in adulthood. Not only immature neurons are able to precisely control the expression of a plethora of genes necessary for axon extension and pathfinding, synapse formation and function, but also non‐neuronal cells such as astrocytes and microglia actively participate in sculpting the nervous system through refinement, consolidation, and elimination of synaptic contacts. Recent evidence indicates that a balancing act between axon regeneration and synaptic function may be crucial for rebuilding functional neuronal circuits after CNS trauma and disease in adulthood. Here, we review the role of classical and new intrinsic and extrinsic neuronal determinants in the context of CNS development, injury, and disease. Moreover, we discuss strategies targeting neuronal and non‐neuronal cell behaviors, either alone or in combination, to promote axon regeneration and neuronal circuit formation in adulthood.